Molecular landscape of myelodysplastic neoplasms in disease classification and prognostication. Issue 2 (30th March 2023) - Maggioni, Giulia; Della Porta, Matteo G.
Abstract : Purpose of review: The aim of this review is to provide a complete perspective of the evidence that led to the three recent new landmarks of myelodysplastic syndromes (MDS) definition and prognostication: the WHO 2022 and International Consensus Classification (ICC) 2022 classification and the Molecular Intermational Prognostic Scoring System (IPSS-M) score. Recent findings: The molecular founding lesions of MDS are strongly linked with disease phenotype and prognosis, therefore the genetic assessment have become part of MDS classifications and prognostication. Summary: The WHO 2022 now recognizes the class 'MDS with defining genetic abnormalities'. It includes 'MDS with SF3B1 mutation', and 'MDS with biallelic TP53 inactivation'. The ICC 2022 further introduces the category 'MDS/acute myeloid leukemia (AML)' emphasizing the biological continuum existing between the diseases, with the aim to expand therapeutic possibilities for MDS patients with more than 10% of blasts; it further identifies 9 MDS-funding lesions, defying the 'MDS/AML with myelodysplasia-related gene mutations' class. In recent years, many efforts have been done in order to specify and weight the role of mutations in disease prognostication; the IPSS-M proposed in 2022 finally integrates the molecular profile of the disease with the clinical and cytogenetic data, providing a better prognostication at patient level compared to IPSS-R.